Silvopastoral use of Nothofagus antarctica in Southern Patagonian forests, influence over net nitrogen soil mineralization - Bahamonde, Héctor Alejandro; Peri, Pablo Luis; Alvarez, Roberto; Barneix, Atilio Jose; Moretto, Alicia Susana; Martínez Pastur, Guillermo José (2018)
In most temperate forest, nitrogen (N) is considered a limiting factor. This becomes important in extreme environments, as Nothofagus antarctica forests, where the antecedents are scarce. Thinning practices in N. antarctica forests for silvopastoral uses may modify the soil N dynamics. Therefore, the objective of this work was to evaluate the temporal variation of soil N in these ecosystems. The mineral extractable soil N, net nitrification and net N mineralization were evaluated under different crown cover and two site quality stands. The mineral N extractable (NH4 +–N + NO3 −–N) was measured periodically. Net nitrification and net N mineralization were estimated through the technique of incubation of intact samples with tubes. The total mineral extractable N concentration varied between crown cover and dates, with no differences among site classes. The lowest and highest values were found in the minimal and intermediate crown cover, respectively. In the higher site quality stand, the annual net N mineralization was lower in the minimal crown cover reaching 11 kg N ha−1 year−1, and higher in the maximal crown cover (54 kg N ha−1 year−1). In the lower site quality stand there was no differences among crown cover. The same pattern was found for net nitrification. Thinning practices for silvopastoral use of these forests, keeping intermediate crown cover values, did not affect both N mineralization and nitrification. However, the results suggest that total trees removal from the ecosystem may decrease N mineralization and nitrification.